2010
DOI: 10.1007/s00795-010-0514-3
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of estrogen receptor-α upregulation in breast cancers

Abstract: The most critical step for initiation and progression of estrogen receptor-α (ERα)-positive breast cancers is thought to be upregulation of ERα expression. There are several factors involved in this mechanism, i.e., increased promoter activity of the ERα gene (ESR1) at the transcriptional level, ESR1 gene amplification, and diminished degradation of ERα protein through ubiquitination and proteasomal pathways. Mediating these factors, ERα protein levels seem to be controlled, although the details of the mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 22 publications
0
29
0
Order By: Relevance
“…These results suggest that Tamoxifen up-regulates ERa expression by increasing promoter activity of the ERa gene (Ers1) at the transcriptional level [12].…”
Section: Discussionmentioning
confidence: 83%
“…These results suggest that Tamoxifen up-regulates ERa expression by increasing promoter activity of the ERa gene (Ers1) at the transcriptional level [12].…”
Section: Discussionmentioning
confidence: 83%
“…ERs consist of two isoforms, ERα and ERβ, which have been identified to be expressed in multiple tissues, including the mammary gland (19). ERα is the primary type of ER in breast tissues, and is encoded by the ESR1 gene (20). High expression levels of ERα correlate with increased mRNA levels of ESR1 (19).…”
Section: A B C Dmentioning
confidence: 99%
“…Studies using ER knockout animal models have shown that ER α is the predominant mediator of mitogenic effects of oestrogen in the breast [69] , and it tends to be ER α , which is expressed at highest levels in ER + breast cancers [70] . However, the majority of ER α -positive breast tumours also contain ER β , and in its role as a putative tumour suppressor, ER β can act to ameliorate the proliferative effects of ER α such that tumours with increased levels of ER β compared to ER α can have a more favourable prognosis [71,72] .…”
Section: Differential Effects Through Alteration To Relative Levels Omentioning
confidence: 99%